How many species of genus Lernaeopoda Blainville, 1822 (Siphonostomatoida: Lernaeopodidae) are there in the southwestern Atlantic? - Montes, Martin M.; Gómez, Sebastián; Castro, Raúl R.; Bovcon, Nelson; Vettorazzi, Renzo I.; Serrano, Claudio F.; Cardarella, German F. Reig; Ferrari, Walter; Cuevas, Juan Martin; Martorelli, Sergio R. (Zootaxa, 2023)
The family Lernaeopodidae includes 14 genera parasitizing elasmobranchs. Fourteen species of this family have been cited from Argentina, four of which were found on chondrichthyans. Schroederichthys bivius Müller and Henle and Galeorhinus galeus (Linnaeus) from Argentina harbored parasitic copepods of the genus Lernaeopoda. The objective of this study was to identify the species using an integrative approach. The morphology was examined by Optical Microscopy and Scanning Electron Microscopy and the molecular analysis was based on partial sequences of the COI mtDNA gene. Despite differences in the antenna, antennule, mandible, maxilliped and maxillae among the specimens, the morphological and molecular analyses revealed that they belonged to Lernaeopoda bivia Leigh-Sharpe, 1930. The species so far reported for Argentina are L. bivia and L. galei Krøyer, 1837, which are distinguished by the size (less and greater than 7 mm, respectively). Here, we report partial sequences of the COI mtDNA gene of L. bivia for the first time, obtained from eleven specimens attached to the mouth, fins, anal slit and claspers of the two shark hosts. The COI mtDNA gene tree shows that the Lernaeopoda group forms a sister clade with Pseudocharopinus bicaudatus (Krøyer, 1837), while the genus Pseudocharopinus does not appear to be a natural group. We propose that the material described from Argentinean waters as L. galei was misidentified and actually belongs to L. bivia. The wide variability within the specimens of L. bivia emphasizes the importance of using an integrative approach to revise the taxonomy of the Lernaeopoda species from all over the world.